2022
DOI: 10.1038/s41386-022-01268-7
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of impaired emotion inhibition in bipolar disorder mediated by cholinergic neurotransmission in the cingulate cortex

Abstract: The muscarinic-cholinergic system is involved in the pathophysiology of bipolar disorder (BD), and contributes to attention and the top-down and bottom-up cognitive and affective mechanisms of emotional processing, functionally altered in BD. Emotion processing can be assessed by the ability to inhibit a response when the content of the image is emotional. Impaired regulatory capacity of cholinergic neurotransmission conferred by reduced M2-autoreceptor availability is hypothesized to play a role in elevated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Furthermore, adding more samples to this analysis improved effect size estimates for each tract. Abnormal FA in anterior portions within the cingulum is consistent with the regions where activations are detected in emotion-related fMRI studies in BD [33]. Morphological and network-based connectivity studies have reported deficits in FA in the limbic right anterior and subgenual cingulate cortex [34].…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, adding more samples to this analysis improved effect size estimates for each tract. Abnormal FA in anterior portions within the cingulum is consistent with the regions where activations are detected in emotion-related fMRI studies in BD [33]. Morphological and network-based connectivity studies have reported deficits in FA in the limbic right anterior and subgenual cingulate cortex [34].…”
Section: Discussionsupporting
confidence: 74%
“…Our regional findings implicate fronto-limbic and interhemispheric connections in BD. FA alterations, in anterior sections within the cingulum, are in regions where activations are detected in emotion-related fMR studies in BD [39], among other morphological and connectivity studies [16]. Additionally, alterations in the corpus callosum have been consistently found in structural, diffusion and functional MR studies of BD, particularly within the anterior horn (connecting bilateral prefrontal and limbic regions) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactivity in this region may thus reflect a stronger distress-related pain-empathic reactivity or a stronger need to regulate the negative affective experience. 22,68 Increasing number of reports indicated that individuals with mental disorders experience greater levels of empathic distress 69,70 and the role of this region in the experience of pain-related emotional distress findings may reflect higher pain empathic reactivity. The vACC subregion of the ACC has moreover been found to play an important role in other related functions such as social cognitive decision-making, behavior encoding, and outcome prediction 71,72 and can mediate the saliency of the external stimuli thus triggering pain empathic experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Etkin et al, 2011a; Xiang et al, 2018). Hyperactivity in this region may thus reflect a stronger distress-related pain-empathic reactivity or a stronger need to regulate the negative affective experience (Betti and Aglioti, 2016; Nabulsi et al, 2022). The increasing number of reports indicated that individuals with mental disorders experience greater levels of empathic distress (Allman et al, 2001; Apps et al, 2016) and the role of this region in the experience of pain-related emotional distress findings may reflect higher pain empathic reactivity.…”
Section: Discussionmentioning
confidence: 99%